2023
DOI: 10.3390/polym15112460
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties Optimization of Hybrid Aramid and Jute Fabrics-Reinforced Graphene Nanoplatelets in Functionalized HDPE Matrix Nanocomposites

Abstract: Natural lignocellulosic fibers (NLFs) have been used as a reinforcement for polymer matrix composites in the past couple of decades. Their biodegradability, renewability, and abundance make them appealing for sustainable materials. However, synthetic fibers surpass NLFs in mechanical and thermal properties. Combining these fibers as a hybrid reinforcement in polymeric materials shows promise for multifunctional materials and structures. Functionalizing these composites with graphene-based materials could lead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Notably, the utilization of GNPs demonstrated superior effectiveness in enhancing the fracture toughness compared with other nanomaterials. Costa et al [ 37 ] reported the improvement of the tensile strength of a high-density polyethylene-based FRPC with natural fibers by incorporating GNPs into the matrix. An increase of over 20% in the Young’s modulus was achieved compared with the high-density polyethylene composite alone, reaching 1.63 ± 0.15 GPa.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the utilization of GNPs demonstrated superior effectiveness in enhancing the fracture toughness compared with other nanomaterials. Costa et al [ 37 ] reported the improvement of the tensile strength of a high-density polyethylene-based FRPC with natural fibers by incorporating GNPs into the matrix. An increase of over 20% in the Young’s modulus was achieved compared with the high-density polyethylene composite alone, reaching 1.63 ± 0.15 GPa.…”
Section: Introductionmentioning
confidence: 99%